Lipid-encapsulated mRNA encoding an extended serum half-life interleukin-22 ameliorates metabolic disease in mice - Susanna Canali; Alexander W. Fischer; Mychael Nguyen; Karl Anderson; Lorna Wu; Anne-Renee Graham; Chiaowen Joyce Hsiao; Chinmayi Bankar; Nancy Dussault; Veronica Ritchie; Meagan Goodridge; Todd Sparrow; et al. (Elsevier, 2024)
Objective: Interleukin (IL)-22 is a potential therapeutic protein for the treatment of metabolic diseases such as obesity, type 2 diabetes, and metabolic dysfunction-associated steatotic liver disease due to its involvement in multiple cellular pathways and observed hepatoprotective effects. The short serum half-life of IL-22 has previously limited its use in clinical applications; however, the development of mRNA-lipid nanoparticle (LNP) technology offers a novel therapeutic approach that uses a host-generated IL-22 fusion protein. In the present study, the effects of administration of an mRNA-LNP encoding IL-22 on metabolic disease parameters was investigated in various mouse models. Methods: C57BL/6NCrl mice were used to confirm mouse serum albumin (MSA)-IL-22 protein expression prior to assessments in C57BL/6NTac and CETP/ApoB transgenic mouse models of metabolic disease. Mice were fed either regular chow or a modified amylin liver nonalcoholic steatohepatitis-inducing diet prior to receiving either LNP-encapsulated MSA-IL-22 or MSA mRNA via intravenous or intramuscular injection. Metabolic markers were monitored for the duration of the experiments, and postmortem histology assessment and analysis of metabolic gene expression pathways were performed. Results: MSA-IL-22 was detectable for ≥8 days following administration. Improvements in body weight, lipid metabolism, glucose metabolism, and lipogenic and fibrotic marker gene expression in the liver were observed in the MSA-IL-22-treated mice, and these effects were shown to be durable. Conclusions: These results support the application of mRNA-encoded IL-22 as a promising treatment strategy for metabolic syndrome and associated comorbidities in human populations.